The study of the relationship of indicators of immune status and serum ferritin in patients with thalassemia. - Rakhmanova, U. U.; Suleymanova, D.N.; Shamsutdinova, M.I.; Masharipova, I.Yu.; Ishchanova, N.H. (International Journal of Psychosocial Rehabilitation, 2020)
Data on increased susceptibility to infections with thalassemia have generated interest in studying the immune status of patients with beta-thalassemia. The state of cellular and humoral immunity and the amount of iron-containing ferritin protein were studied in 200 patients, girls and boys with various forms of thalassemia. The indicators of humoral immunity, immunoglobulins A, M, G, as well as some indicators of cellular immunity CD3+, CD4+, CD8+, CD16+ were determined. Determination of immunoglobulins A, M, G was carried out by enzyme-linked immunosorbent assay on an apparatus of Human GmbH (Germany). Indicators of humoral immunity show a decrease in immunoglobulin A, but immunoglobulins M and G are elevated. Normally, ferritin is -10-120 ng / ml, and according to the results of our study, the content of serum ferritin is -1513.1 ng / ml, this indicator is 12.6 times higher, which indicates a risk of developing hemosiderosis of internal organs.